1995
DOI: 10.1111/j.1365-2141.1995.tb05308.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in chronic myeloid leukaemia: normal responses by progenitor cells to growth factor deprivation, X‐irradiation and glucocorticoids

Abstract: Inhibition of apoptosis (genetically programmed active cell death) by p210 BCR-ABL expression is a mechanism that might contribute to clonal expansion in chronic myeloid leukaemia (CML). Since cell death following exposure to ionizing radiation and many chemotherapeutic agents can occur by the apoptotic pathway, inhibition of apoptosis would be expected to confer a relative resistance to these treatments. Similarly, cells deprived of growth factors in vitro die by apoptosis, and inhibition of apoptosis would t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 30 publications
2
47
0
1
Order By: Relevance
“…Similarly, Bedi and colleagues (1994) showed that hematopoietic progenitors from CML patients are relatively resistant to induction of apoptosis, and that antisense treatment can sensitize these cells. This resistance to apoptosis of hematopoietic progenitors from CML patients is, however, controversial (Amos et al, 1995). More recently, Bedi and colleagues (1995) have suggested that the anti-apoptotic effect of Bcr-Abl is related to a delayed progression through G2/M, allowing time for DNA repair and prevention of mitotic catastrophe.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Bedi and colleagues (1994) showed that hematopoietic progenitors from CML patients are relatively resistant to induction of apoptosis, and that antisense treatment can sensitize these cells. This resistance to apoptosis of hematopoietic progenitors from CML patients is, however, controversial (Amos et al, 1995). More recently, Bedi and colleagues (1995) have suggested that the anti-apoptotic effect of Bcr-Abl is related to a delayed progression through G2/M, allowing time for DNA repair and prevention of mitotic catastrophe.…”
Section: Discussionmentioning
confidence: 99%
“…33 The heterogeneity of patient samples and the potential differences of BCR-ABL protein expression, which varies from one patient (and probably from one hematopoietic cell) to another, could explain discordant findings obtained with regard to the inhibition of apoptosis in primary patient samples. 9,10 Our model distinctly shows that: (1) BCR-ABL protein expression in a human hematopoietic cell line is not sufficient to induce growth factor independence; and (2) the anti-apoptotic effect of BCR-ABL is fully operational only when BCR-ABL is expressed at high levels. Our data confirm, therefore, for the first time in pluripotent human cells, the results obtained by Pierce et al 34 in the murine FDCP-mix cell line in which the tyrosine kinase activity of BCR-ABL was found to be compatible with growth factor dependence and differentiation ability.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] It has been established that BCR-ABL triggers a variety of molecular events inside the target cell with activation of several molecular pathways such as RAS, PI-3K and CRK-L. 4 evance with regard to human CML in which there have been conflicting reports with regard to the anti-apoptotic effects of BCR-ABL. [7][8][9][10] Similarly, although BCR-ABL gene transfer induces growth factor independence in growth factor-dependent cell lines, human hematopoietic progenitors bearing the BCR-ABL translocation as assessed by PCR or FISH analyses are not growth factor-independent and present only subtle abnormalities such as Epo-independent erythroid colony growth 11 in the presence of Steel factor. 12 Anti-apoptotic activities of BCR-ABL have been shown to be reverted by inhibition of the tyrosine kinase activity of BCR-ABL.…”
Section: Introductionmentioning
confidence: 99%
“…62,63,73 Most but not all studies using p210 BCR/ABL expressing cell lines have demonstrated that BCR-ABL expression protects from apoptosis induced by physical and chemical stresses. [74][75][76][77][78] Additionally, chronic phase CML CD34 + cells undergo delayed apoptotic death upon cytokine withdrawal when compared with normal progenitors. [79][80][81] The use of antisense oligonucleotides against BCR-ABL could reverse the delay in apoptosis in CML cell lines.…”
Section: Decreased Apoptosismentioning
confidence: 99%